The Effect of Sustainable Development Goals Implementation and Corporate Governance on Sustainability Report Transparency with Firm Size as a Moderating Variable: Analysis of the consumer goods sector Listed on the Indonesia Stock Exchange, 2022-2024 - Winda Rahmawati; Ihsan Nasihin; Dhea Imroatul Fatihah (Sanskara Akuntansi dan Keuangan, 2026)
In this study, we will look at consumer goods companies listed on the Indonesia Stock Exchange from 2022 to 2024 to see how corporate governance and the SDGs affect the transparency of sustainability reports. We will use company size as a moderating variable to determine the exact impact. This research used quantitative methods to go through secondary data such as annual reports and company sustainability reports. With a total of 99 participants, the study employed purposive sampling. The statistical procedures employed included MRA and multiple linear regression. Transparency in sustainability reporting is positively and significantly impacted by SDG implementation, but by corporate governance, no such effect was observed. When it comes to the impact of SDG implementation and corporate governance on sustainability reporting transparency, organizational size might not be a determining factor. In general, the implementation of the SDGs has a greater influence on the openness of sustainability reporting than corporate governance and firm size. These results show that a key element in raising the transparency of sustainability report is a company's dedication to sharing sustainability-related information.